Measuring Filial Piety in the 21st Century: Development, Factor Structure, and Reliability of the 10-Item Contemporary Filial Piety Scale. (November 2016) - Lum, Terry Y. S.; Yan, Elsie C. W.; Ho, Andy H. Y.; Shum, Michelle H. Y.; Wong, Gloria H. Y.; Lau, Mandy M. Y.; Wang, Junfang
The experience and practice of filial piety have evolved in modern Chinese societies, and existing measures fail to capture these important changes. Based on a conceptual analysis on current literature, 42 items were initially compiled to form a Contemporary Filial Piety Scale (CFPS), and 1, 080 individuals from a representative sample in Hong Kong were surveyed. Principal component analysis generated a 16-item three-factor model: Pragmatic Obligations (Factor 1; 10 items), Compassionate Reverence (Factor 2; 4 items), and Family Continuity (Factor 3; 2 items). Confirmatory factor analysis revealed strong factor loadings for Factors 1 and 2, while removing Factor 3 and conceptually duplicated items increased total variance explained from 58.02% to 60.09% and internal consistency from .84 to .88. A final 10-item two-factor structure model was adopted with a goodness of fit of 0.95. The CFPS-10 is a data-driven, simple, and efficient instrument with strong psychometric properties for assessing contemporary filial piety.